Common visual problems in children with disability. Issue 12 (27th August 2014) - Salt, Alison; Sargent, Jenefer
Abstract : Children with disability are at a substantially higher risk of visual impairment (VI) (10.5% compared with 0.16%) but also of ocular disorders of all types, including refractive errors and strabismus. The aetiology of VI in children with disability reflects that of the general population and includes cerebral VI, optic atrophy, as well as primary visual disorders such as retinal dystrophies and structural eye anomalies. VI and other potentially correctable ocular disorders may not be recognised without careful assessment and are frequently unidentified in children with complex needs. Although assessment may be more challenging than in other children, identifying these potential additional barriers to learning and development may be critical. There is a need to develop clearer guidelines, referral pathways and closer working between all professionals involved in the care of children with disability and visual disorders to improve our focus on the assessment of vision and outcomes for children with disability.